The impact of financial subsidies and tax incentives on corporate innovation: A systematic literature review based on Citespace - Liu, Qiuhong; Othman, Rani Diana; Kamarudin, Siti Nurhazwani (Edelweiss Applied Science and Technology, 2025)
From the global economic development perspective, innovation has become a crucial driving force for economic growth. The entire world is transitioning smoothly into the digital era and experiencing a profound wave of scientific innovation, with increased intensity in research and development investments worldwide. However, there is a lack of systematic analysis regarding the developmental trends of the impact of financial subsidies and tax incentives on corporate innovation. Employing CiteSpace, this study comprehensively utilizes bibliometric analysis and content analysis methods to review 51 articles selected from the Web of Science and Scopus databases. The analysis involves examining the characteristics and content of the literature. It identifies the overall publication landscape, trends in research hotspots, and clustering of research themes. The study also provides a qualitative analysis of research outcomes on the impact of financial subsidies and tax incentives on corporate innovation, considering dimensions such as research questions, research methods, and research conclusions. The findings reveal advancements in research on the impact of financial subsidies and tax incentives on innovation performance, innovation efficiency, innovation input and output, technological innovation, and innovations related to environmental sustainability. In conclusion, it looks forward to the future development trends of this research theme, focusing on the introduction of innovation quality, strengthening interactive impact analysis, and expanding the exploration of moderating variables.